Methods and Lines of Research on Latin Linguistic: Vulgar Latin (Minerva, 2017)
The following pages offer a perspective about the methods and main lines of research on Latin Linguistics, mainly concerning to Vulgar Latin. Therefore, different methodological trends in Romance Philology and Latin Philology will be reviewed. Special analysis will be on those currents fitting more with the study of the Vulgar Latin and its peculiarities, by pointing out the objectives and results of those lines of research from a critical perspective.
Keywords: vulgar latin; romance philology; methods; lines of research; variation; extralinguistic